INSTRUCTIONAL CHOICES TO HEIGHTEN INDONESIAN STUDENTS' MOTIVATION AND ENGAGEMENT IN READING ENGLISH CANONICAL TEXTS - Yosep Bambang Margono (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
This paper focuses on how to motivate my struggling students for whom English is a second language when they read canonical texts written in English. Students in English departments are required to read English canonical texts, but most of them find this task very challenging. One strategy teachers can use to motivate students to read is to pair the English canonical texts with young adult texts. Important in these instructional choices are the pre-reading, during-reading, and after-reading activities. Pre-reading activities are intended to prepare readers to enter the story world During-reading activities are important to make students understand the stories better. Some of the duringactivities include using role plays and teaching media to increase students' understanding of the characters and the plots in the books. In the post-reading activities, students can write journals or quotes they find interesting from the book. Giving students more varieties in book choices and activities can, hopefully, make them independent good readers.